2011
DOI: 10.1002/cphc.201100187
|View full text |Cite
|
Sign up to set email alerts
|

A DFT Investigation of Surface‐Enhanced Raman Scattering of Adenine and 2′‐Deoxyadenosine 5′‐Monophosphate on Ag20 Nanoclusters

Abstract: We present a detailed analysis of the surface-enhanced Raman scattering (SERS) of adenine and 2'-deoxyadenosine 5'-monophosphate (dAMP) adsorbed on an Ag(20) cluster by using density functional theory. Calculated Raman spectra show that spectral features of all complexes depend greatly on adsorption sites of adenine and dAMP. The complexes consisting of adenine adsorbed on the Ag(20) cluster through N3 reproduce the measured SERS spectra in silver colloids, and thus demonstrated that adenine interacts with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…It is reported that SERS enhancements have been observed up to the power of 15 in single molecule experiments. [2] It is generally accepted that SERS effect is interpreted by electromagnetic and chemical enhancement. Electromagnetic enhancement arises from enhanced electric fields at the surface of particles due to plasmon resonance excitation.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that SERS enhancements have been observed up to the power of 15 in single molecule experiments. [2] It is generally accepted that SERS effect is interpreted by electromagnetic and chemical enhancement. Electromagnetic enhancement arises from enhanced electric fields at the surface of particles due to plasmon resonance excitation.…”
Section: Introductionmentioning
confidence: 99%
“…[40], except tetrahedral A g20 which had been studied before in Refs. [41][42][43]. Binding energies have been obtained including the counterpoise method to correct for the basis set superposition error (BSSE) [44,45].…”
Section: Computational Detailsmentioning
confidence: 99%
“…This interaction can be analyzed by means of vibrational spectroscopy because it provides more specific information of the adsorbate. However, the ordinary Raman spectroscopy is basically unable to identify the properties of adsorbed organic and bio-molecules because of its low scattering intensity [14]. This inconvenience can be effectively overcome by resorting to surface-enhanced Raman spectroscopy (SERS) [15,16], in which, ordinary weak Raman scattering can be significantly enhanced when there is chemical adsorption of the analyte molecule on the surface of new metals [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, the ordinary Raman spectroscopy is basically unable to identify the properties of adsorbed organic and bio-molecules because of its low scattering intensity [14]. This inconvenience can be effectively overcome by resorting to surface-enhanced Raman spectroscopy (SERS) [15,16], in which, ordinary weak Raman scattering can be significantly enhanced when there is chemical adsorption of the analyte molecule on the surface of new metals [14]. SERS is a phenomenon in which the scattering cross sections of probe molecules adsorbed on the surface of the metal is increased [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation